Globalizing the Classroom: Innovative Approach to National and International Learning. (May 2015) - Bell, Patricia; Coates, Rodney; Colombo, Enzo; Dolgon, Corey; Hernandez, Sarah; Margulis, Matias E.; Nyamathi, Adey; Pavlish, Carol; Romo, Harriett
This essay examines an innovative approach to teaching across international and cultural boundaries and evaluates the experience in a course on Globalization, Social Justice, and Human Rights, co-taught collaboratively by faculty from different campuses and countries since 2011. This course was created to address unmet needs in the traditional higher educational systems. These include, but are not limited to, lack of cross-cultural and interdisciplinary collaboration among students, faculty, and institutions. Although economies, polities, environments, and human societies are experiencing great connections across the globe, educational systems continue to be modeled on nineteenth century assumptions and structures. In this course, faculty teach at their respective universities but use an online platform to allow for cross-campus communication. In addition to the classroom rooted in a physical place, a major component of student work is to interact online with students on other campuses, including undertaking collaborative group work across borders. A shared core syllabus can be modified by institution to satisfy local needs. In this essay, we examine the following: the history and logistics of this course; the facilitators and barriers in its implementation, including the use of technology; the role of language and communication; and the mechanisms necessary for faculty to adopt such a collaborative, global effort to local curricular guidelines. We also address the benefits of the course for students, including exposure to global diversity (culture, worldviews, and pedagogy); developing teamwork skills such as leadership and flexibility; accepting and accommodating diverse educational needs/approaches; and promoting interdisciplinary communication and collaboration. Finally, we assess the challenges for faculty in designing and managing a course across different time zones and academic calendars, facilitating transnational group service learning projects, and the greater time demands required to coordinate and monitor students' online interactions. Our objective is to help improve and encourage innovative approaches to teaching globalization, social justice, and human rights.